IMPROVING AWARENESS OF INTERNET SECURITY AND ETHICS AMONG STUDENTS AT SMA NEGERI 2 MRANGGEN - Naufal, Muhammad; Hidayat, Novianto Nur; Trisnapradika, Gustina Alfa; Al Azies, Harun (Universitas Airlangga, 2025)
This community service initiative aimed to enhance the awareness of internet security and ethics among high school students at SMA Negeri 2 Mranggen, Demak Regency, Central Java. The program utilized a structured methodology consisting of outreach, training, and evaluation stages conducted in a hands-on environment within the school's computer laboratory. The training covered key topics such as data security, phishing attacks, malware, and ethical internet use. The sessions were held in the school’s computer laboratory to provide hands-on experience. Each training session had a duration of 3×45 minutes, attended by 31 students, allowing comprehensive exploration of the material. Pre- and post-tests were administered to assess the effectiveness of the training. The results demonstrated a significant improvement in students' knowledge, with average scores increasing from 49 in the pre-test to 72.67 in the post-test. A paired t-test analysis confirmed this improvement as statistically significant, with a T-statistic of -13.971 and a P-value of 2.07 × 10-14. The findings highlight the program's success in raising awareness and equipping students with the skills to navigate the digital world safely and responsibly. This initiative underscores the importance of educational programs in fostering internet literacy and security awareness among young users. To build on these findings, it is recommended that similar training sessions to be conducted regularly to reinforce the concepts learned. Additionally, a long-term plan is proposed as a form of sustainability of this community service program, namely by expanding the training targets not only to students but also to teachers, housewives and children who are already accustomed to gadgets.